Monetary policy and the punch bowl: The case for quantitative policy and wage growth targeting - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2017)
Federal Reserve Chairman William McChesney Martin famously declared that the Federal Reserve "is in the position of the chaperone who has ordered the punch bowl removed just when the party was really warming up." This paper uses the punch bowl metaphor to analyze how the Federal Reserve can improve monetary policy so as to deliver shared prosperity with greater financial stability. The problem is the party starts earlier on Wall Street than Main Street, so the Fed may remove the punchbowl before the party reaches Main Street. Ensuring Main Street attends the party requires a new recipe for the punch, new serving rules, and a new punch master. Additionally, there is a deeper problem that current neoliberal growth model has the economy addicted to monetary punch. Resolving that requires a cure that goes beyond the punch bowl. – – William McChesney Martin, ehemaliger Präsident der amerikanischen Notenbank Federal Reserve, hat die Geldpolitik einmal wie folgt charakterisiert: "Die Fed ist in der Position der Anstandsdame, die die Bowle entfernen lässt, sobald die Party richtig losgeht." Der vorliegende Artikel baut die Bowle-Metapher aus, um zu analysieren, wie die Federal Reserve die Geldpolitik so verbessern kann, dass sie sowohl gemeinsamen Wohlstand, als auch finanzielle Stabilität erreicht. Das Problem ist, dass die Party im Finanzsektor startet und die Fed daher die Bowle entfernen könnte, bevor sie die Realwirtschaft erreicht. Um sicherzustellen, dass die Realwirtschaft an der Party teilnimmt, braucht man ein neues Bowle-Rezept, neue Servierregeln und einen neuen Schankwart. Das zusätzliche, tieferliegende Problem ist, dass das gegenwärtige, neoliberale Wachstumsmodell die Wirtschaft von monetärer Bowle abhängig gemacht hat. Dieses Problem kann nur gelöst werden, indem man über das Ausschenken von Alkoholika hinausgeht.
urn:nbn:de:101:1-201707123495
Keywords: 330; monetary policy; punch bowl; quantitative regulation; asset based reserve requirements; policy rules; wage targeting